Pakistan : The First Twelve Years - Khan, Mazhar Ali (Karachi Oxford University Press, 1996)
This posthumous selection of Mazhar Ali Khan's writings is based almost entirely on editorials contributed to The Pakistan Times from 1947 to 1959. The volume intends not only to preserve a distinguished body of work, but also to give historians, scholars, and students access to a lucid and fearlessly critical contemporary perspective of Pakistani politics in the nation's formative years. The majority of editorials deal with the misadventures and intrigues that distinguished politics in Pakistan's first twelve years.
Include Index and Epilogue.
Keywords: Politics and Government -- Pakistan -- Politics and Government